Barriers of Adherence and Possible Solutions to Nonadherence to Antidiabetic Therapy in Women with Diabetes in Pregnancy: Patients’ Perspective - Doreen Mukona; Stephen Peter Munjanja; Mathilda Zvinavashe; Babil Stray-Pederson (Journal of Diabetes Research)
Diabetes in pregnancy contributes to maternal mortality and morbidity though it receives little attention in developing countries. The purpose of the study was to explore the barriers to adherence and possible solutions to nonadherence to antidiabetic therapy in women with diabetes in pregnancy. Antidiabetic therapy referred to diet, physical activity, and medications. Four focus group discussions (FGDs), each with 7 participants, were held at a central hospital in Zimbabwe. Included were women with a diagnosis of diabetes in pregnancy, aged 18 to 49 years, and able to speak Shona or English. Approval was obtained from respective ethical review boards. FGDs followed a semistructured questionnaire. Detailed notes were taken during the interviews which were also being audiotaped. Data were analysed thematically and manually. Themes identified were barriers and possible solutions to nonadherence to therapy. Barriers were poor socioeconomic status, lack of family, peer and community support, effects of pregnancy, complicated therapeutic regimen, pathophysiology of diabetes, cultural and religious beliefs, and poor health care system. Possible solutions were fostering social support, financial support, and improvement of hospital services. Individualised care of women with diabetes is essential, and barriers and possible solutions identified can be utilised to improve care.